UPA‐uPAR molecular complex is involved in cell signaling during neuronal migration and neuritogenesis. Issue 5 (19th February 2014) - Lino, Noelia; Fiore, Luciano; Rapacioli, Melina; Teruel, Luisa; Flores, Vladimir; Scicolone, Gabriel; Sánchez, Viviana
<x xml:space="preserve">Abstract</x> Background: In the development of the central nervous system (CNS), neuronal migration and neuritogenesis are crucial processes for establishing functional neural circuits. This relies on the regulation exerted by several signaling molecules, which play important roles in axonal growth and guidance. The urokinase‐type plasminogen activator (uPA)—in association with its receptor—triggers extracellular matrix proteolysis and other cellular processes through the activation of intracellular signaling pathways. Even though the uPA‐uPAR complex is well characterized in nonneuronal systems, little is known about its signaling role during CNS development. Results: In response to uPA, neuronal migration and neuritogenesis are promoted in a dose‐dependent manner. After stimulation, uPAR interacts with α5‐ and β1‐integrin subunits, which may constitute an αβ‐heterodimer that acts as a uPA‐uPAR coreceptor favoring the activation of multiple kinases. This interaction may be responsible for the uPA‐promoted phosphorylation of focal adhesion kinase (FAK) and its relocation toward growth cones, triggering cytoskeletal reorganization which, in turn, induces morphological changes related to neuronal migration and neuritogenesis. Conclusions: uPA has a key role during CNS development. In association with its receptor, it orchestrates both proteolytic and nonproteolytic events that govern the proper formation of neural networks. Developmental Dynamics 243:676–689, 2014. © 2014 Wiley Periodicals, Inc.